The international strengthening of IPR and air pollution abatement: the role of the TRIPs agreement - Di Vita, Giuseppe (Technological and Economic Development of Economy, 2017)
This paper comes in the wake of the literature considering technological progress as the main device to offset air pollution caused by economic activity. The issue has been extensively studied in general, but there is no previous research on the effects that an international strengthening of legal protection of Intellectual Property Rights (IPR) due to the Uruguay Round Agreement and the Annex on Trade-Related aspects of the IPR (TRIPs, for short), underwritten in 1994, may have had on worldwide emissions, as a result of the discovery of new or more efficient air pollution abatement technologies. Different econometric models are used to give a quantitative measure of the TRIPs agreement to reduce air pollution. In particular, the impact of the TRIPs is addressed using a dummy variable and the index of Ginarte and Park (Ginarte, Park 1997) that is one of the more commonly used indicators of TRIPs enforcement employed in economic literature. The findings of this research partially support the idea that the strengthening of a uniform minimum standard protection level of IPR, among the member countries of the World Trade Organization, may help to reduce air pollution emissions. First published online: 03 Nov 2015